America right or wrong : an anatomy of American nationalism - Lieven, Anatol (Oxford University Press, 2005)
In this controversial critique of American political culture and its historical roots, Anatol Lieven contends that U.S. foreign policy since 9/11 has been shaped by the special character of our nationalism. Within that nationalism, Lieven analyses two very different traditions. One is the "American thesis," a civic nationalism based on the democratic values of what has been called the "American Creed." These values are held to be universal, and anyone can become an American by adopting them. The other tradition, the "American antithesis" is a populist and often ch.